Solution (1) :
Given, to find A we have to :
- square m
- Add y to m²
- Subtract 7 from m² + y
From the question, the following equation can be formed :
![=\tt A = {m}^(2) + y - 7](https://img.qammunity.org/2022/formulas/mathematics/college/otuvrdmyefyuohc29tuuaszcdofu7sg2vl.png)
Therefore, the formula for finding A = m² + y - 7
Solution (2) :
The value of A we can derive from the formula is :
![=\tt A = {m}^(2) + y - 7](https://img.qammunity.org/2022/formulas/mathematics/college/otuvrdmyefyuohc29tuuaszcdofu7sg2vl.png)
Value of m = 3 (given)
Which means :
![=\tt A = {3}^(2) + y - 7](https://img.qammunity.org/2022/formulas/mathematics/college/fbkp6td5bg4s7lzp60ifp0qw6wtppklmmx.png)
![=\tt \: A = 9 + y - 7](https://img.qammunity.org/2022/formulas/mathematics/college/cupy5uxgvrmh5bu3zo55ro77uv8pwcxw2f.png)
![=\tt A = 9 - 7 + y](https://img.qammunity.org/2022/formulas/mathematics/college/1cmlgp767lho3c6c6yg45nfya3xo4l1erh.png)
![\color{plum} =\tt A = 2 + y](https://img.qammunity.org/2022/formulas/mathematics/college/6255at6xyw4go586thi2zctd548wqpm0yn.png)
Thus, the value of A = 2+y
Therefore, the value of A = 2+y